Understanding the Urgent Need for Subtitling for the Deaf and Hard of Hearing in the Spanish-Speaking Greater Antilles - Fuentes-Luque, Adrián; González-Irizarry, Pabsi Livmar (Journal of Audiovisual Translation, 2020)
Even though Audiovisual Translation (AVT) is growing and flourishing throughout the world, it is practically unheard-of in the Caribbean, where accessibility faces an even bleaker existence. The circumstances of the deaf and hard of hearing (also referred to as D/deaf) are no less alarming: social barriers and exclusion are widespread. This paper emphasizes the need to make subtitles accessible in the Spanish-speaking Caribbean, specifically on the islands of Puerto Rico, Cuba, and the Dominican Republic, and underscores the challenges faced by the D/deaf communities on each island. Our research focuses on issues like AVT laws and regulations, the habits of viewers of audiovisual (AV) products, and literacy and limitations on each island. This paper also examines the different types of D/deaf audiovisual consumers in the Spanish-speaking Caribbean and the difficulties each community faces when accessing media and entertainment. Our research reveals the current state of AVT accessibility in this region and provides a foundation for influencing legislators to begin enforcing AVT regulations and drafting SDH guidelines.